Menemukenali Leksikon-leksikon Arkais pada Bidang Obat-obatan Tradisional Bali - Netra, I Made (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
This article aims to identify types of archaic lexicon in the Balinese cultural practices of traditional medicine and configure their meanings. Data were obtained by participatory observation method with note-taking and recording techniques. Lists of archaic lexicons existing in 10 fields of Balinese cultural practices were taken from a questionnaire given to 80 respondents spread in Buleleng and Gianyar districts. The analysis showed that 11 archaic lexicons were found in the field of Balinese traditional medicine. They are classified into archaic lexicons because of the incomprehension of the younger generation regarding the existence of their artifacts and use in society even though they are still found and used in rural areas. Therefore, they are not yet categorized as extinct.  The conceptual configuration of the lexicon can be made based on a cultural scripts approach with the "if ...... then" component and exponent description, such as entities, ways of creation, results, and functions Keywords: archaic lexicon, artifacts, medicine, young generation, geographical areas